Employee Empowerment in Order to Increase the Professionalism Index - Panggabean, Sahat Nicolus Wicaksono; Anggraini, Alverina Wikke; Raharja, Edy (LifeSciFi, 2024)
Law Number 5 of 2014 regulates the management of Civil Servants (Aparatur Sipil Negara/ASN), with the principle of professionalism serving as one of the foundations of public service effectiveness. Professionalism is defined as the reliability in task execution, ensuring high-quality performance that is timely, precise, and appropriate for the public. In simpler terms, professionalism is the behaviour, methods, and qualities that characterize a profession. Data shows that the effectiveness of the Indonesian government, including the professionalism of its civil servants, still needs improvement. According to the National Civil Service Agency (Badan Kepegawaian Negara/BKN), the measurement of the ASN Professionalism Index (Indeks profesionalitas Aparatur Sipil Negara/IPASN) is based on four dimensions: educational qualifications, competencies, performance, and discipline. Nationally, the IPASN score remains in the low-to-medium range. As a government institution, the Center for Drug and Food Control in Semarang (Balai Besar Pengawas Obat dan Makanan/BBPOM in Semarang) has a strong interest in improving its organizational IPASN score. This study uses a qualitative approach to examine BBPOM in Semarang's success in enhancing its IPASN score by empowering civil servants in the areas of educational qualifications, competencies, performance, and discipline. The success of BBPOM in Semarang can serve as a practical reference for empowering civil servants to improve their IPASN.